Technology Transfer 20.000€ - Keivanidis, Panagiotis E. (My University, 2026)
Principle investigator of a 20.000€ technology transfer project with the industrial entity SAES Getters s.l.r., Lainate (IT) for developing a spectroscopic technique to monitor oxygen permeation in next generation oxygen-barrier materials for organic electronic devices.
Keywords: Natural sciences